Students’ Strategies to Decrease Anxiety in Speaking English Class at the Sixth Semester of the Informatics Engineering Study Program - Hadi, Dholiful; Yuliasari, Ulfa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aimed to know the students’ strategies to decrease anxiety in speaking English class at the sixth semester of the informatics engineering study program. The researcher used descriptive method because it is referred to describe the students’ strategy anxiety. To collect the data, the instrument used in this study are classroom observations and questionnaire. The findings reveal that students engage in positive self-talk, visualization, regular practice, and relaxation techniques to boost their confidence. Peer support and feedback also play significant roles in creating a supportive learning environment. Classroom observations highlight the importance of a positive classroom atmosphere fostered by encouraging lecturers and collaborative activities. Additionally, the use of technology and institutional resources such as counseling services are found to be effective in reducing language anxiety.The questionnaire given includes five strategies namely preparation, relaxation, positive thinking, peer seeking, and resignation. The respondent of this research was the sixth semester of the informatics engineering study program which consisted of 32 students. So the researcher can conclude that the students gave agree about the strategy to reduce anxiety in speaking English. Where the strategy makes students can improve their skills, especially in speaking skills and make the students used the strategy where they speaking English. The research findings showed that students' agreement of Preparation was 101, Relaxation 117, Positif Thinking 121, Peer Seeking 110 and Resignation 108. It can be assumed that the percentage of human experience was 63%, for Preparation, 73% for Relaxation, 75% for Positive Thinking, 68,75 for Peer Seeking and 67,50% for Resignation